Graphene biosensor as affinity biosensors for biorecognition between Guanine riboswitch and ligand - Tian, Meng; Li, Zhenhua; Song, Ruihong; Li, Yingxian; Guo, Chengang; Sha, Yujie; Cui, Wanling; Xu, Shicai; Hu, Guodong; Wang, Jihua (Applied surface science, 2020)
•G-FET biosensor was developed to detect the binding interactions between GR and ligand molecules.•Mechanisms for electric-neutral molecule sensing was revealed by molecular dynamics simulation.•Equilibrium dissociation constants KD and binding free energy ΔG of GR and ligand molecules were obtained. Guanine riboswitch (GR) is located in the untranslated region of mRNA that performs important biological functions by interactions with specific ligand molecules. The present standard methods for detecting mRNA has been widely used, but suffer from extra labeling steps, high cost, low throughput, low sensitivities and limited dynamic ranges. The field effect transistor (FET) biosensors showed high performance in detecting a large number of biological analytes. However, the detection of analytes with low charge and small molecule still remains a challenge. In this paper, a label-free graphene field effect transistor (G-FET) biosensor has been developed to detect the binding interactions between GR and four purine analog ligand molecules (GUA, 6GU, 2BP, XAN). We demonstrated that the G-FET biosensor were highly sensitive in detecting the electric-neutral and low molecular weight ligands by using GR as probe. The sensing mechanisms for electric-neutral molecule is revealed by molecular dynamics simulation. The equilibrium dissociation constants KD and binding free energy ΔG of GR-GUA, GR-6GU, GR-2BP and GR-XAN were obtained by the G-FET biosensor, and the results are comparable with the calculated by molecular dynamics simulation and previous reports. We demonstrated that the G-FET biosensor can be used as affinity biosensors to quantify biomolecular interactions.